2002
DOI: 10.1074/jbc.m109219200
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Release of Histones from Nucleosomes

Abstract: Chromatin structure is influenced by histone modification, and this may help direct chromatin behavior to facilitate transcription, DNA replication, and DNA repair. Chromatin condensation and DNA fragmentation are the classic nuclear features but remain poorly characterized. It is highly probable that nucleosomal structure must be altered to allow these features to become apparent, but data to support this construct are lacking. We report here that in response to apoptotic signals from a death receptor (CD95 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
3
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 34 publications
6
90
3
1
Order By: Relevance
“…Previous studies have shown that histones are released in various apoptotic cells [46,47]. Our findings indicate that 1) histones are also released in isolated nuclei treated with Ca 2+ and 2) the amount of histones released corresponds approximately to the amount of internucleosomal DNA.…”
Section: Chromatin Structure In Isolated Nuclei Treated With Ca 2+supporting
confidence: 64%
“…Previous studies have shown that histones are released in various apoptotic cells [46,47]. Our findings indicate that 1) histones are also released in isolated nuclei treated with Ca 2+ and 2) the amount of histones released corresponds approximately to the amount of internucleosomal DNA.…”
Section: Chromatin Structure In Isolated Nuclei Treated With Ca 2+supporting
confidence: 64%
“…In this disease, defective clearance of apoptotic cells has been considered to play a role in its pathogenesis (49,50). Interestingly, recent studies also indicate that, during apoptosis, histones (H1, H2A, H2B, H3, and H4) are released from chromatin, leading to the formation of naked DNA (51). In this study, we provide evidence that DNA on apoptotic cell surfaces binds HRG and affects HRG-dependent binding and ingestion of apoptotic cells.…”
Section: Discussionmentioning
confidence: 54%
“…These results support the concept that histone release into the cytoplasm was not merely a consequence of DNA fragmentation, and agree with the fact that apoptosis could be detected in apoptotic cells that did not present DNA frag- © F e r r a t a S t o r t i F o u n d a t i o n mentation. 17 To summarize, histone H1.2 release into the cytoplasm in CLL cells could represent a novel and common step in apoptosis induced by different stimuli. Importantly, this new apoptotic effector is abrogated when using DNA damaging agents in highly deleted 17p13 cases.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Konishi et al recently reported new insights into the death signal transmission pathway. 18 They demonstrated the apoptogenic ability of histone H1.2 when this protein translocated from the nucleus into the cytosol after DNA double-strand breaks.…”
Section: Introductionmentioning
confidence: 99%